Influence of Adolescence and Obesity on the Rate of Stillbirth. Issue 4 (17th June 2013) - Warshak, Carri R.; Wolfe, Katherine B.; Russell, Kimberly A.; Habli, Mounira; Lewis, David F.; DeFranco, Emily A.
Abstract Background We hypothesise that the rate of stillbirth is increased in mothers younger than 18 years of age compared to adult mothers, and that obesity further increases the risk of stillbirth in this population. Methods We conducted a population‐based cohort study comparing rates of stillbirth between adolescent, defined as young women under the age of 18 and adult women. We then compared the rate of stillbirth in normal weight vs. obese adolescents. These effects were stratified according to gestational age. Log‐binomial regression models were used to estimate the effect of adolescence and obesity on stillbirth risk while adjusting for important confounders. Risk ratios (RR) with 95% confidence intervals [CI]were calculated. Results We reviewed data from 650 760 births in Missouri between 1998 and 2005. Stillbirth rates were 6.7 and 4.1 per 1000 in adolescents and adult women, respectively (RR 1.2, 95% CI 1.03–1.5). A higher proportion of stillbirths occurred prior to 28 weeks in adolescents vs. adults (53% vs. 37% respectively, P = 0.002). The risk of stillbirth in obese adolescents was further increased over normal weight adolescents (adjusted RR [aRR] 1.7, 95% CI 1.02–2.9). Conclusion Adolescent pregnancies, particularly obese adolescents, are at an increased risk of stillbirth.